Magnetic Fusion Technology - Dolan, Thomas J. (Lecture Notes in Energy, 2013)
Magnetic Fusion Technology describes the technologies that are required for successful development of nuclear fusion power plants using strong magnetic fields. These technologies include: ⬢ magnet systems, ⬢ plasma heating systems, ⬢ control systems, ⬢ energy conversion systems, ⬢ advanced materials development, ⬢ vacuum systems, ⬢ cryogenic systems, ⬢ plasma diagnostics, ⬢ safety systems, and ⬢ power plant design studies. Magnetic Fusion Technology will be useful to students and to specialists working in energy research.